COVID-19 -A NEW PANDEMIC FOR 137 MILLION INDIAN - IMPACT, INTERVENTIONS AND SOLUTIONS - CHOUDHERY, ANIS A.; KHATIB, SUMAIYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Objective: There were many historical epidemics in India in the last century. COVID-19 is a new- age epidemic, which we have never experienced in the near past. The objective of our research is to highlight the effect of a pandemic, the impact of interventions, and to propose a concrete and useful mitigation plan for India to fight not only this epidemic but also for other disasters. We need to re-assess our strategies, planning and available tools to fight with this pandemic and the crisis due to pandemic. Methods: This present study based on a literature review available for public reference as well as interviews conducted with different sections of society. Case studies of two nations- South Korea and Taiwan, which are successful in containing the pandemic, were reviewed. Literatures were sourced from reliable public domain sources and official government data. Results: India may be successfully handling COVID-19 but at a significant cost. It is expected that lakhs of people will suffer from it, possibly thousands will die, but indeed 1.3 billion Indians will be affected directly or indirectly. It could have been avoided. We have included success stories of two triumphant nations Taiwan and South Korea, for their excellent use of technology during combat against COVID-19. Conclusion: We concluded this study with scientific and social feedback to the government about their existing pandemic management program and helping them in building an innovative disaster management communication tool for the future. Our strategic, structured program, IFDM -Indian Firewall for Disaster Management, is the outcome of this research.